2015
DOI: 10.3390/app5041955
|View full text |Cite
|
Sign up to set email alerts
|

Main Leaf Polyphenolic Components of Berry Color Variant Grapevines and Their Acclimative Responses to Sunlight Exposure

Abstract: Grapevine leaf synthesizes a wide variety of bioactive secondary metabolites, including polyphenols, which are also key components in ensuring development and growth of the whole plant even under adverse environmental conditions. Our study evaluates the nonanthocyanin polyphenolic composition in grapevine leaves of three varieties of Gohér conculta (Vitis vinifera L.) native to Hungary. A high performance liquid chromatography (HPLC) system including a diode array detector (DAD) coupled to a time-of-flight mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…Total phenols content in white varieties is slightly higher than in red varieties (138 and 131 mg GAE g À1 respectively). The same result was verified in other studies where white and red grapevine leaf varieties were compared considering their phenolic content (Fernandes et al, 2013;Koesis et al, 2015). Total phenols content varied between 112 mg GAE g À1 (Gouveio) and 150 mg GAE g À1 (Fernão Pires).…”
Section: Phenolic Groups Contentsupporting
confidence: 62%
See 1 more Smart Citation
“…Total phenols content in white varieties is slightly higher than in red varieties (138 and 131 mg GAE g À1 respectively). The same result was verified in other studies where white and red grapevine leaf varieties were compared considering their phenolic content (Fernandes et al, 2013;Koesis et al, 2015). Total phenols content varied between 112 mg GAE g À1 (Gouveio) and 150 mg GAE g À1 (Fernão Pires).…”
Section: Phenolic Groups Contentsupporting
confidence: 62%
“…Leaves from both studies were collected in different regions, with possible different edaphoclimatic conditions. For instance, the light exposure increases phenolic accumulation in leaf tissues (Koesis et al, 2015), as well as the radiation received by leaves change the phenolic content (Kolb & Pfündel, 2005).…”
Section: Phenolic Groups Contentmentioning
confidence: 99%
“…These levels in general agree with reports that grapevine leaves are rich sources of flavonols. In their studies, [2,20,22,79,84,85] found that the predominant phenolics in the leaves are quercetin-3-O-glucuronide, quercetin-3-O-glucoside, caftaric acid, and kaempferol-3-O-glucoside; total amounts of quercetin derivatives were significantly higher than total amounts of kaempferol derivatives in the studies [2,79,85]. The 40 stilbenes reported in the leaves of V. vinifera are eminently less abundant than the phenolic acids and flavonoids.…”
Section: Phenolic Compounds In Grapevine Leavesmentioning
confidence: 95%
“…This is reported that AS 195 has been used for edema preventing effects in the early stages of CVI (Güthenke, 1960). One of the most active compounds of AS 195 includes the flavonoids (e.g., quercetin‐3‐O‐b‐glucuronide, isoquercitrin (quercetin‐3‐O‐b‐glucoside) (Kiesewetter et al, 2000; Kocsis et al, 2015) and kaemperol‐3‐O‐b‐D‐glucosid) (Kocsis et al, 2015). Flavonoids have been shown to improve symptoms and signs related to CVI (Struckmann, 1999).…”
Section: Introductionmentioning
confidence: 99%